The Ex-Terrorist Social Reintegration Based on Community Participation Through a Corporate Social Responsibility Program - Pratama, I Gusti Agung Ananta; Madjid, Abdul; Aprilianda, Nurini; Istiqomah, Milda (Audito Comparative Law Journal (ACLJ), 2024)
This study examines how former terrorism convicts or prisoners can be integrated into society using the company's CSR funding help strategy. The author discovers a gap in regulatory standards because the Terrorism Law solely governs measures to prevent and suppress terrorism. This research aims to provide an overview of the reform of the Terrorism Law and the social reintegration model for former convicts using an empirical research model that involves interviewing sources. The findings of this study suggest that the Terrorism Law should be amended and the BNPT reimagined as an entity dedicated to preventing terrorist attacks in Indonesia.